PENGEMBANGAN PERANGKAT EVALUASI BERBASIS ANDROID UNTUK SISWA SEKOLAH DASAR KELAS VI DI SD TRIDARMA BUDHIDAYA - Amalia Nabila Salim; M Hosnan; M Taufik (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
This study aims to develop an Android-based evaluation device for grade VI elementary school students. This research was conducted at SD Tridarma Budhidaya North Jakarta City in the academic year 2019/2020. This research uses the Research and Development (R&D) method. The product produced from this research is an evaluation device. This evaluation device is software that is made using WEB by using Android as a supporting tool. Testing the feasibility in this media, an expert validation trial was conducted. Expert validation was carried out by media experts with research subjects namely all grade VI students of SD Tridarma Budhidaya North Jakarta as many as 13 students. From the data obtained, this Android-based evaluation device gets an average score of expert validation of 94.15%, so that it gets the category of "very feasible", and gets an average score of 94% of student responses and falls into the criteria of "very good ", Subsequently scored 87% of the responses of teachers who get the criteria of" very good ". So it can be concluded that this android-based evaluation tool is feasible and can be used in grade VI students of elementary schools.